Irreparable rotator cuff tears: Current treatment options - Juhan, Tristan (Orthop Rev (Pavia), 2019)
Rotator cuff disease is one of the most common causes of shoulder pain, yet controversy still exists regarding treatment of “irreparable” tears. Nonoperative management, including physical therapy and steroid injections, should be reserved for those without significant pain or functional impairment. Debridement may be used for low-demand patients, and should be performed with partial cuff repair, subacromial decompression, and/or acromioplasty to maximize outcomes. Biceps tenotomy and/or tenodesis have been shown to reduce postoperative pain and improve satisfaction when performed in conjunction with rotator cuff repairs, with no difference in functional outcome comparatively. Tendon transfers have been advocated with the potential benefit to improve function and decrease pain. More recently, extracellular matrix and human-derived dermal allografts have been used off-label as patch grafts in irreparable tears. Superior capsular reconstructive techniques and subacromial balloon spacers serve a similar function by acting to depress the humeral head in a cuff-deficient shoulder, however long-term data is needed before widespread adoption of these procedures. Finally, reverse shoulder arthroplasty serves as a salvage option for low demand elderly patients.